Photorefractive materials : - Frejlich, Jaime (Wiley-Interscience, 2007)
Photorefractive Materials presents an overview of the basic features and properties of photorefractive materials, covering a wide array of related topics. It provides a coherent approach suitable for introductory and advanced students seeking to learn or review the fundamentals, as well as senior researchers who need a reference while investigating more specialized areas.